Non-Ischemic, Non-Hypoxic Myocardial Injury, and Long-Term Mortality in Patients with Coronavirus Disease 2019: A Retrospective Cohort Study - Fajiu Li; Xijie Zhu; Ziyang Zhu; Yinjian Yang; Zhuang Tian; Duolao Wang; Shi Chen; Xiaoyan Gao; Yalin Xu; Bo Zhang; Wei Yu; Min Liu; et al. (Cardiology Discovery)
Abstract. Objective:. Cardiac damage is commonly reported in patients with coronavirus disease 2019 (COVID-19) but its prevalence and impact on the long-term survival of patients remain uncertain. This study aimed to explore the prevalence of myocardial injury and assess its prognostic value in patients with COVID-19. Methods:. A single-center, retrospective cohort study was performed at the Affiliated Hospital of Jianghan University. Data from 766 patients with confirmed COVID-19 who were hospitalized from December 27, 2019 to April 25, 2020 were collected. Demographic, clinical, laboratory, electrocardiogram, treatment data and all-cause mortality during follow-up were collected and analyzed. Results:. Of the 766 patients with moderate to critically ill COVID-19, 86 (11.2%) died after a mean follow-up of 72.8 days. Myocardial injury occurred in 94 (12.3%) patients. The mortality rate was 64.9% (61/94) and 3.7% (25/672) in patients with and without myocardial injury, respectively. Cox regression showed that myocardial injury was an independent risk factor for mortality (hazard ratio: 8.76, 95% confidence interval: 4.76–16.11, P < 0.001). Of the 90 patients with myocardial injury with electrocardiogram results, sinus tachycardia was present in 29, bundle branch block in 26, low voltage in 10, and abnormal T-wave in 53. Conclusions:. COVID-19 not only involves pneumonia but also cardiac damage. Myocardial injury is a common complication and an independent risk factor for mortality in COVID-19 patients.